2020
DOI: 10.3390/jcm9030674
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Method for Forecasting Confirmed Cases of COVID-19 in China

Abstract: In December 2019, a novel coronavirus, called COVID-19, was discovered in Wuhan, China, and has spread to different cities in China as well as to 24 other countries. The number of confirmed cases is increasing daily and reached 34,598 on 8 February 2020. In the current study, we present a new forecasting model to estimate and forecast the number of confirmed cases of COVID-19 in the upcoming ten days based on the previously confirmed cases recorded in China. The proposed model is an improved adaptive neuro-fuz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
324
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(332 citation statements)
references
References 58 publications
1
324
0
7
Order By: Relevance
“…Wu et al (2020) predicted the spread of COVID-19 for the national and global scale, to evaluate the effect of the metropolitan-wide quarantine of Wuhan and its neighbours . Al-qaness et al (2020) improved the Adaptive Neuro-Fuzzy Inference System (ANFIS) by applying an Enhanced Flower Pollination Algorithm using the Salp Swarm Algorithm to estimate the number of confirmed COVID-19 cases in China (Al-qaness et al, 2020). Anastassopoulou et al (2020) studied on the estimation of the critical epidemiological parameters as well as the modeling and predicting the spread of the COVID-19 epidemic in Hubei, China (Anastassopoulou et al, 2020).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Wu et al (2020) predicted the spread of COVID-19 for the national and global scale, to evaluate the effect of the metropolitan-wide quarantine of Wuhan and its neighbours . Al-qaness et al (2020) improved the Adaptive Neuro-Fuzzy Inference System (ANFIS) by applying an Enhanced Flower Pollination Algorithm using the Salp Swarm Algorithm to estimate the number of confirmed COVID-19 cases in China (Al-qaness et al, 2020). Anastassopoulou et al (2020) studied on the estimation of the critical epidemiological parameters as well as the modeling and predicting the spread of the COVID-19 epidemic in Hubei, China (Anastassopoulou et al, 2020).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…The estimated of number of cases was obtained by back calculation method [22]. They found that the best method for modeling and estimating the number of total cases was the FPASSA-ANFIS method [23].…”
Section: Discussionmentioning
confidence: 99%
“…• Given the systemic immunosuppressive state caused by malignancy and anticancer treatments, patients with advanced lung cancer may be at a higher risk of COVID-19 infection [15]. • Results of MTT assay revealed that seven synthesized compounds (i.e., 11a, 11b, 12a, 12b, 13b, 13c and 13h) particularly exhibited significant cytotoxicity against the three cancerous cell lines under investigation [16].…”
Section: Cancermentioning
confidence: 99%